2018
DOI: 10.3390/challe9010017
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterials and Oxidative Stress

Abstract: With the rapid development of new nanomaterials, it was recognized early that together with their beneficial properties, nanomaterials may pose a risk to human health and the environment. Evidence has accumulated over the last twenty years in support of oxidative stress as a broad mechanistic concept to explain the interaction of engineered nanoparticles with biological substances. As oxidative stress as a physiological response was recognized in redox biology, its wide-ranging use in nanotoxicology has expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
(43 reference statements)
1
2
0
Order By: Relevance
“…33 Photocatalytic titanium dioxide nanoparticles can generate highly reactive hydroxyl radicals that damage DNA, 34 and cells that experience extreme oxidative stress die through programmed cell death. 35 In our research, the TEM results showed hollowing in the Fon cells treated with AgNP/NSP and NSP. In addition, propidium iodide stain assay demonstrated that AgNP/NSP and NSP increased Fon cell membrane permeability significantly.…”
Section: ■ Results and Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…33 Photocatalytic titanium dioxide nanoparticles can generate highly reactive hydroxyl radicals that damage DNA, 34 and cells that experience extreme oxidative stress die through programmed cell death. 35 In our research, the TEM results showed hollowing in the Fon cells treated with AgNP/NSP and NSP. In addition, propidium iodide stain assay demonstrated that AgNP/NSP and NSP increased Fon cell membrane permeability significantly.…”
Section: ■ Results and Discussionsupporting
confidence: 51%
“…Application of silver nanoparticles affects mitochondrial function and induces reactive oxygen species accumulation that leads to oxidative stress . Photocatalytic titanium dioxide nanoparticles can generate highly reactive hydroxyl radicals that damage DNA, and cells that experience extreme oxidative stress die through programmed cell death . In our research, the TEM results showed hollowing in the Fon cells treated with AgNP/NSP and NSP.…”
Section: Resultsmentioning
confidence: 51%
“…Oxidative stress is widely studied in biomedical toxicology [ 56 ]. Experiments designed to simulate an oxidative environment typically involve incubations with a particular concentration of a chemical oxidizer.…”
Section: Methods To Prepare and Analyze Reference Materialsmentioning
confidence: 99%